β-Glucan-Induced IL-10 Secretion by Monocytes Triggers Porcine NK Cell Cytotoxicity - Hermans, Leen; De Pelsmaeker, Steffi; Denaeghel, Sofie; Cox, Eric; Favoreel, Herman W.; Devriendt, Bert (Frontiers in Immunology, 2021)
Beta glucans are naturally occurring polysaccharides present in cell walls of fungi, yeast, bacteria, cereals, seaweed and algae. These microbe-associated molecular patterns (MAMPs) possess immunomodulatory properties. In human, it has been suggested that NK cells can be activated by β glucans. Here, we aimed to elucidate whether β glucans modulate porcine NK cell responses in vitro and if so, how these effects are mediated. We investigated the effect of two β glucans, Macrogard and Curdlan, which differ in solubility and structure. Direct addition of β glucans to purified porcine NK cells did not affect cytotoxicity of these cells against K562 target cells. However, when using PBMC instead of purified NK cells, β glucan addition significantly increased NK cell-mediated cytotoxicity. This effect depended on factors secreted by CD14+ monocytes upon β glucan priming. Further analysis showed that monocytes secrete TNF-α, IL-6 and IL-10 upon β glucan addition. Of these, IL-10 turned out to play a critical role in β glucan-triggered NK cell cytotoxicity, since depletion of IL-10 completely abrogated the β glucan-induced increase in cytotoxicity. Furthermore, addition of recombinant IL-10 to purified NK cells was sufficient to enhance cytotoxicity. In conclusion, we show that β glucans trigger IL-10 secretion by porcine monocytes, which in turn leads to increased NK cell cytotoxicity, and thereby identify IL-10 as a potent stimulus of porcine NK cell cytotoxicity.